INTERACTIVE VISUAL NARRATIVES IN QUECHUA: AN ARTISTIC AND TECHNOLOGICAL STRATEGY TO STRENGTHEN LINGUISTIC IDENTITY IN NURSING STUDENTS WITHIN A FORMATIVE RESEARCH CONTEXT - Paucar-Curasma, Ronald (Seven Editora, 2025)
The incorporation of Indigenous languages into higher education represents both a challenge and an opportunity to strengthen cultural identity and improve communication in professional fields such as health. This study aimed to develop an interactive visual narrative in the Quechua language as an artistic and technological resource within a formative research process involving nursing students at a public university in Peru. The proposal was grounded in the Problem- and Technology-Based Research (IBPT) approach and employed block-based programming in mBlock along with a STEM educational kit to design interactive simulations addressing air quality in households that use firewood stoves—a common health concern in Andean communities. A total of 64 students participated by designing a Quechua-language digital narrative connected to environmental sensors and completing a post-test assessing linguistic comprehension and perceptions of using Quechua in educational and technological contexts. Results showed a medium-high level of Quechua comprehension (mean score of 3.58/5 on content questions) and a highly positive perception of integrating the language into academic activities (average scores above 4.0 on perception items). Findings indicate that interactive visual narratives are effective tools for integrating technology, art, and Indigenous language, fostering meaningful learning, strengthening cultural identity, and enhancing the social relevance of health education. The study concludes that incorporating Indigenous languages into context-based technological projects supports epistemological decolonization, the development of digital competencies, and intercultural professional training in nursing students.DOI: https://doi.org/10.56238/sevened2025.036-129